2012
DOI: 10.1099/vir.0.042572-0
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Toll-like receptor 3 confer natural resistance to human herpes simplex virus type 2 infection

Abstract: Lack of Toll-like receptor 3 (TLR3) functional activity predisposes children to human herpesvirus 1 (HSV-1) encephalitis. In this study, we have investigated whether there is any link between TLR3 and adult HSV-2 infection by studying genetic variations in TLR3. The frequency of four singlenucleotide polymorphisms (SNPs) in the TLR3 gene in 239 patients with genital HSV-2 infection and 162 healthy controls, as well as the impact of these variants on TLR3 gene-expression levels, were compared. Two SNPs in the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 31 publications
0
26
1
1
Order By: Relevance
“…HCV infection A [52] HSV infection G [53] HIV infection G [54] Tick-borne encephalitis virus infection G [55] TLR7 rs179008 A > T Gln11Leu HCV T [56] HIV infection T [57] TLR8 rs3764880 G > A Val1Met Tuberculosis A [58,59] Crimean-Congo hemorrhagic fever G TLR5 forms homodimers for the recognition of bacterial flagellin (Table 1). The TLR5 gene is located on chromosome 1.…”
Section: Toll-like Receptorsmentioning
confidence: 98%
“…HCV infection A [52] HSV infection G [53] HIV infection G [54] Tick-borne encephalitis virus infection G [55] TLR7 rs179008 A > T Gln11Leu HCV T [56] HIV infection T [57] TLR8 rs3764880 G > A Val1Met Tuberculosis A [58,59] Crimean-Congo hemorrhagic fever G TLR5 forms homodimers for the recognition of bacterial flagellin (Table 1). The TLR5 gene is located on chromosome 1.…”
Section: Toll-like Receptorsmentioning
confidence: 98%
“…Notably, our study also revealed an association of an intronic TLR3 poly- morphism (rs13126816) with the expression of TLR3 and the clearance of HCV. This intronic SNP, previously reported to be associated with rubella virus-specific cytokine responses (21) and herpesvirus (22), is distinct from a common polymorphism in the TLR3 coding region that affects responses in chronic HCV infection (46) and to the neurotropic herpesvirus (40,47,48). In murine models, TLR3 mediates robust cytokine responses to the related flavivirus West Nile virus (49) and to influenza A virus (although such responses are detrimental in that context [50]) for cross-priming of viral antigens to cytotoxic T cells (51).…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was purified from whole-blood or peripheral blood mononuclear cell (PBMC) samples of all study subjects using the QIAamp DNA Blood Midi or Mini kit (Qiagen, Inc.). Single nucleotide polymorphism (SNP) selection was based upon information available at the dbSNP (U.S. National Center for Biotechnology Information; http://www.ncbi.nlm.nih.gov /SNP/) and in published findings (19)(20)(21)(22)(23). Four SNPs (minor allele frequency of Ͼ0.2) located in human TLR3 (rs13126816, rs3775291, rs5743303, and rs5743305) and one SNP in interleukin 28B (IL28B) (rs12979860) were selected for genotyping using TaqMan SNP genotyp- ing assays according to the manufacturer's instructions (Applied Biosystems, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…The amino acid change from Isoleucine to Asparagine (N284I) is associated with A851T (rs5743316) while the change from Phenylalanine to Leucine (L412F) is associated with C1234T (rs3775291) (Ranjith-Kumar et al, 2007). TLR3 [rs3775291:L412F] polymorphism has been associated with various viral infections and non-viral diseases/states (Kindberg et al, 2011;Gorbea et al, 2010;Sironi et al, 2012;O'Dwyer et al, 2013;Citores et al, 2011;Ishizaki et al, 2008;Nahum et al, 2011;Zhou et al, 2011;Svensson et al, 2012). We hypothesize that abnormalities in TLR3 genes and its functioning may increase the susceptibility of patients for JE.…”
Section: Introductionmentioning
confidence: 96%